Metal-Amplified Density Assays, (MADAs), including a Density-Linked Immunosorbent Assay (DeLISA). Issue 4 (4th December 2014) - Subramaniam, Anand Bala; Gonidec, Mathieu; Shapiro, Nathan D.; Kresse, Kayleigh M.; Whitesides, George M.
Abstract : This paper reports a method of conducting quantitative and/or multiplexed assays, including immunoassays, by measuring metal-amplified changes in the density of protein-adsorbed beads using Magnetic Levitation (MagLev). Abstract : This paper reports the development of Metal-amplified Density Assays, or MADAs – a method of conducting quantitative or multiplexed assays, including immunoassays, by using Magnetic Levitation (MagLev) to measure metal-amplified changes in the density of beads labeled with biomolecules. The binding of target analytes ( i.e. proteins, antibodies, antigens) to complementary ligands immobilized on the surface of the beads, followed by a chemical amplification of the binding in a form that results in a change in the density of the beads (achieved by using gold nanoparticle-labeled biomolecules, and electroless deposition of gold or silver), translates analyte binding events into changes in density measureable using MagLev. A minimal model based on diffusion-limited growth of hemispherical nuclei on a surface reproduces the dynamics of the assay. A MADA – when performed with antigens and antibodies – is called a Density-Linked Immunosorbent Assay, or DeLISA. Two immunoassays provided a proof of principle: a competitive quantification of the concentration of neomycin in whole milk, and a multiplexed detection of antibodies against Hepatitis C virus NS3 protein and syphilis T. pallidum p47 protein in serum. MADAs, including DeLISAs, require, besides the requisite biomolecules and amplification reagents, minimal specialized equipment (two permanent magnets, a ruler or a capillary with calibrated length markings) and no electrical power to obtain a quantitative readout of analyte concentration. With further development, the method may be useful in resource-limited or point-of-care settings.